AL-IJÂRAH AL-MUMTAHIYAH BI AL-TAMLÎK: TELAAH SOSIOLOGIS, FILOSOFIS DAN YURIDIS - Noor Salim, Muhammad Firliadi (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2025)
With the increasing demands of modern life and limited financial resources, rent-to-own transactions have become a popular option for individuals to acquire goods without upfront full payment. While widely adopted by conventional financial institutions, these systems often lead to high-interest burdens, creating financial strain for consumers. In response, Islamic Financial Institutions (IFIs) have sought to develop equitable and Sharia-compliant financing products, such as the al-Ijârah al-Mumtahiyah bi al-Tamlîk (IMBT) contract. This innovative contract combines a lease (ijârah) with a promise of ownership at the end of the lease term, offering a more transparent and just alternative. This study employs a qualitative research methodology with juridical-normative and descriptive-analytical approaches. Data was gathered through literature and document studies, encompassing sources like the Qur'an, Hadith, DSN-MUI fatwas, relevant Indonesian laws and regulations, and Islamic legal and economic literature. The primary focus is to analyze the concept, legal basis, and philosophy of both ijârah and IMBT contracts within the practical context of Islamic financial institutions in Indonesia. This approach facilitates a deep understanding of IMBT's implementation, ensuring it is transparent and free from elements of usury (riba), excessive uncertainty (gharar), and speculation (maysir). The findings demonstrate that the IMBT contract offers a fair and flexible Sharia-compliant financing solution, meeting the modern community's need for asset acquisition. Philosophically, ijârah and IMBT are grounded in principles of justice, mutual consent (ridha), and reciprocal benefit (consensualism), reflecting the interdependent nature of human social and economic interactions. Furthermore, IMBT holds a strong legal foundation within Indonesia's positive legal system, being regulated by various laws and DSN-MUI fatwas. This robust regulatory framework affirms IMBT's status as a legitimate and binding contract that fully adheres to Sharia principles.